2016
DOI: 10.1016/j.bbamem.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The human cathelicidin LL-37 — A pore-forming antibacterial peptide and host-cell modulator

Abstract: The human cathelicidin hCAP18/LL-37 has become a paradigm for the pleiotropic roles of peptides in host defence. It has a remarkably wide functional repertoire that includes direct antimicrobial activities against various types of microorganisms, the role of 'alarmin' that helps to orchestrate the immune response to infection, the capacity to locally modulate inflammation both enhancing it to aid in combating infection and limiting it to prevent damage to infected tissues, the promotion of angiogenesis and wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
231
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(273 citation statements)
references
References 248 publications
11
231
1
11
Order By: Relevance
“…Furthermore, the translation of LL37 to a human immune therapeutic is hampered by its susceptibility to degradation by proteases4748. In contrast, FhHDM-1 is resistant to proteolytic cleavage by human proteases1925, suggesting increased stability and a more attractive pharmacokinetic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the translation of LL37 to a human immune therapeutic is hampered by its susceptibility to degradation by proteases4748. In contrast, FhHDM-1 is resistant to proteolytic cleavage by human proteases1925, suggesting increased stability and a more attractive pharmacokinetic profile.…”
Section: Discussionmentioning
confidence: 99%
“…The most researched of the cationic AMPs reviewed here for potential medical development is LL-37, which is a prospective broad range antimicrobial agent that is also able to induce wound healing and angiogenesis as well as modulate apoptosis [243]. This potential is, however, limited in some cases by the pleiotropic effects of the peptide [244].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%
“…Several studies have shown that peptides from different sources such as sea hare Turner et al, 1998;Madden et al, 2000;Vaishampayan et al, 2000;Woyke et al, 2001), fish sauce (Thang and Zhao, 2015;Bah et al, 2016), and cod (Xhindoli et al, 2016) were able to block proliferation of carcinogenic cells. However, it seems there is still a long way in order to make commercial use of these potentially potent anticancer peptides to treat different kinds of cancer.…”
Section: Cytomodulatory Effectmentioning
confidence: 99%